Radiation Shielding Properties of Synthetic Ca-Al2O3 Polymer Based Composites - Salawu, Mufutau A.; Ayinla, Ibrahim K.; Ezike, Sabastine .C.; Bello, Mojeed O.; Usman, Usman O.; Yussuf, Abdulmojeed O.; Gbolahan, Julius A.; Alabi, Aderemi B. (Journal of Sustainable Materials Processing and Management, 2023)
Ionizing radiation exposure from medical diagnostic equipment, industries, nuclear research facilities, and nuclear weapon development has led to health impacts such as cancer and acute radiation syndrome, necessitating the use of proper radiation shielding. The optical and radiation shielding capabilities of Ca-Al2O3 polymer-based composites were explored in this article. The composites were made by combining synthesized Aluminum oxide (Al2O3) with calcium (Ca) formed from Periwinkle shells, Snail shells, and Seashells and calcining them at 1000 oC for 13 hours. The synthesized Ca-Al2O3 powders were dispersed into polymeric materials in a ratio of 1:1 using an effective melt-mixing process, then cast in a 10 cm by 10 cm square Mold with a thickness of 10 mm and allowed to set overnight at ambient temperature. The composite samples obtained were transferred to the Nigerian Nuclear Regulatory Agency (NNRA) in Ibadan for radiographic examinations and analyses. X-ray transmission through the manufactured composites samples was investigated using a well-collimated point source. The produced x-rays’ initial intensity (Io) was determined. With the sample in front of the detector, the transmitted x-ray beam (I) was measured. The measurements were repeated three times for each composite sample, and the average value was calculated. Using relevant and referenced equations, the linear attenuation coefficient, half-value layer, relaxation length, and absorbance for each sample were calculated. The radiation shielding composites’ x-ray photon absorptions were determined using transmission data by Beer’s Lambert law. The XRF results revealed that the calcined samples were mostly calcium with only a few traces of other elements, with percentage calcium quantities of approximately 32, 37, and 34 for snail shells, seashells, and periwinkle shells, respectively, and the XRD result confirmed the Al2O3 polymorphs at approximately 32o and 57 o and the Aluminum phase at 46 o. For the three radiation shielding composites under investigation, the x-ray photon transmittance is quite low at 40 keV to 60 keV and comparatively high at 100 keV to 200 keV. From 100 keV to 200 keV, the transmittance of periwinkle shells and snail shell calcium sources polymer-based composites was similar, and their differences became significant at lower energies. For Ca-Al2O3 polymer-based composites with calcium contents sourced from seashells, periwinkle shells, and snail shells, the maximum linear attenuation coefficients were 1.0 cm-1, 0.79 cm-1, and 0.65 cm-1, respectively. At 60 keV and below, the radiation shielding composites have the highest attenuation coefficient. The half-value layer (HVL) of all the samples under investigation reduced abruptly at 40 and 60 keV and grew linearly as the energy increased from 100 to 200 keV. The relaxation length is comparatively low at 40 and 60 keV compared to other x-ray sources utilized at higher energies. Each radiation shielding composite’s properties are determined by the amount of calcium present in the samples. Over a certain photon energy range (40 keV–200 keV), the Ca-Al2O3 polymer-based composites with calcium contents sourced from seashells were found to have higher x-ray attenuating characteristics than other composites. The attenuating capacity of all the composites under this study can be enhanced by increasing the radiation shielding composite thickness.